# Bessel’s equation

 $\displaystyle x^{2}\frac{d^{2}y}{dx^{2}}+x\frac{dy}{dx}+(x^{2}-p^{2})y\;=\;0,$ (1)

in which $p$ is a constant (non-negative if it is real), is called the Bessel’s equation.  We derive its general solution by trying the series form

 $\displaystyle y\;=\;x^{r}\sum_{k=0}^{\infty}a_{k}x^{k}\;=\;\sum_{k=0}^{\infty}% a_{k}x^{r+k},$ (2)

due to Frobenius.  Since the parameter $r$ is indefinite, we may regard $a_{0}$ as distinct from 0.

We substitute (2) and the derivatives of the series in (1):

 $x^{2}\sum_{k=0}^{\infty}(r+k)(r+k-1)a_{k}x^{r+k-2}+x\sum_{k=0}^{\infty}(r+k)a_% {k}x^{r+k-1}+(x^{2}-p^{2})\sum_{k=0}^{\infty}a_{k}x^{r+k}\;=\;0.$

Thus the coefficients of the powers $x^{r}$, $x^{r+1}$, $x^{r+2}$ and so on must vanish, and we get the system of equations

 $\displaystyle\begin{cases}{[}r^{2}-p^{2}{]}a_{0}\;=\;0,\\ {[}(r+1)^{2}-p^{2}{]}a_{1}\;=\;0,\\ {[}(r+2)^{2}-p^{2}{]}a_{2}+a_{0}\;=\;0,\\ \qquad\qquad\ldots\\ {[}(r+k)^{2}-p^{2}{]}a_{k}+a_{k-2}\;=\;0.\end{cases}$ (3)

The last of those can be written

 $(r+k-p)(r+k+p)a_{k}+a_{k-2}\;=\;0.$

Because  $a_{0}\neq 0$,  the first of those (the indicial equation  ) gives  $r^{2}-p^{2}=0$,  i.e. we have the roots

 $r_{1}\;=\;p,\quad r_{2}\;=\;-p.$

Let’s first look the the solution of (1) with  $r=p$;  then  $k(2p+k)a_{k}+a_{k-2}=0$,  and thus

 $a_{k}\;=\;-\frac{a_{k-2}}{k(2p+k).}$

From the system (3) we can solve one by one each of the coefficients $a_{1}$, $a_{2}$, $\ldots$  and express them with $a_{0}$ which remains arbitrary.  Setting for $k$ the integer values we get

 $\displaystyle\begin{cases}a_{1}\;=\;0,\quad a_{3}\;=\;0,\;\ldots,\;a_{2m-1}\;=% \;0;\\ a_{2}\;=\;-\frac{a_{0}}{2(2p+2)},\quad a_{4}\;=\;\frac{a_{0}}{2\cdot 4(2p+2)(2% p+4)},\;\ldots,\;\,a_{2m}\;=\;\frac{(-1)^{m}a_{0}}{2\cdot 4\cdot 6\cdots(2m)(2% p+2)(2p+4)\ldots(2p+2m)}\end{cases}$ (4)

(where  $m=1,\,2,\,\ldots$). Putting the obtained coefficients to (2) we get the particular solution

 $\displaystyle y_{1}\;:=\;a_{0}x^{p}\left[\!\frac{x^{2}}{2(2p\!+\!2)}\!+\!\frac% {x^{4}}{2\!\cdot\!4(2p\!+\!2)(2p\!+\!4)}\!-\!\frac{x^{6}}{2\!\cdot\!4\!\cdot\!% 6(2p\!+\!2)(2p\!+\!4)(2p\!+\!6)}\!+-\ldots\right]$ (5)

In order to get the coefficients $a_{k}$ for the second root  $r_{2}=-p$  we have to look after that

 $(r_{2}+k)^{2}-p^{2}\;\neq\;0,$

or  $r_{2}+k\neq p=r_{1}$.  Therefore

 $r_{1}-r_{2}\;=\;2p\;\neq\;k$

where $k$ is a positive integer.  Thus, when $p$ is not an integer and not an integer added by $\frac{1}{2}$, we get the second particular solution, gotten of (5) by replacing $p$ by $-p$:

 $\displaystyle y_{2}\;:=\;a_{0}x^{-p}\!\left[1\!-\!\frac{x^{2}}{2(-2p\!+\!2)}\!% +\!\frac{x^{4}}{2\!\cdot\!4(-2p\!+\!2)(-2p\!+\!4)}\!-\!\frac{x^{6}}{2\!\cdot\!% 4\!\cdot\!6(-2p\!+\!2)(-2p\!+\!4)(-2p\!+\!6)}\!+-\ldots\right]$ (6)

The power series  of (5) and (6) converge for all values of $x$ and are linearly independent  (the ratio $y_{1}/y_{2}$ tends to 0 as  $x\to\infty$).  With the appointed value

 $a_{0}\;=\;\frac{1}{2^{p}\,\Gamma(p+1)},$

the solution $y_{1}$ is called the and denoted by $J_{p}$.  The similar definition is set for the first kind Bessel function of an arbitrary order  $p\in\mathbb{R}$ (and $\mathbb{C}$). For  $p\notin\mathbb{Z}$  the general solution of the Bessel’s differential equation is thus

 $y\;:=\;C_{1}J_{p}(x)+C_{2}J_{-p}(x),$

where  $J_{-p}(x)=y_{2}$  with  $a_{0}=\frac{1}{2^{-p}\Gamma(-p+1)}$.

The explicit expressions for $J_{\pm p}$ are

 $\displaystyle J_{\pm p}(x)\;=\;\sum_{m=0}^{\infty}\frac{(-1)^{m}}{m!\,\Gamma(m% \pm p+1)}\left(\frac{x}{2}\right)^{2m\pm p},$ (7)

E.g. when  $p=\frac{1}{2}$  the series in (5) gets the form

 $y_{1}\;=\;\frac{x^{\frac{1}{2}}}{\sqrt{2}\,\Gamma(\frac{3}{2})}\left[1\!-\!% \frac{x^{2}}{2\!\cdot\!3}\!+\!\frac{x^{4}}{2\!\cdot\!4\!\cdot\!3\!\cdot\!5}\!-% \!\frac{x^{6}}{2\!\cdot\!4\cdot\!6\!\cdot\!3\!\cdot\!5\!\cdot\!7}\!+-\ldots% \right]\;=\;\sqrt{\frac{2}{\pi x}}\left(x\!-\!\frac{x^{3}}{3!}\!+\!\frac{x^{5}% }{5!}\!-+\ldots\right).$

Thus we get

 $J_{\frac{1}{2}}(x)\;=\;\sqrt{\frac{2}{\pi x}}\sin{x};$

analogically (6) yields

 $J_{-\frac{1}{2}}(x)\;=\;\sqrt{\frac{2}{\pi x}}\cos{x},$

and the general solution of the equation (1) for  $p=\frac{1}{2}$  is

 $y\;:=\;C_{1}J_{\frac{1}{2}}(x)+C_{2}J_{-\frac{1}{2}}(x).$

In the case that $p$ is a non-negative integer $n$, the “+” case of (7) gives the solution

 $J_{n}(x)\;=\;\sum_{m=0}^{\infty}\frac{(-1)^{m}}{m!\,(m+n)!}\left(\frac{x}{2}% \right)^{2m+n},$

but for  $p=-n$  the expression of $J_{-n}(x)$ is $(-1)^{n}J_{n}(x)$, i.e. linearly dependent on $J_{n}(x)$.  It can be shown that the other solution of (1) ought to be searched in the form  $y=K_{n}(x)=J_{n}(x)\ln{x}+x^{-n}\sum_{k=0}^{\infty}b_{k}x^{k}$.  Then the general solution is  $y:=C_{1}J_{n}(x)+C_{2}K_{n}(x)$.

Other formulae

The first kind Bessel functions of integer order have the generating function $F$:

 $\displaystyle F(z,\,t)\;=\;e^{\frac{z}{2}(t-\frac{1}{t})}\;=\;\sum_{n=-\infty}% ^{\infty}J_{n}(z)t^{n}$ (8)

This function  has an essential singularity at  $t=0$  but is analytic elsewhere in $\mathbb{C}$; thus $F$ has the Laurent expansion in that point.  Let us prove (8) by using the general expression

 $c_{n}\;=\;\frac{1}{2\pi i}\oint_{\gamma}\frac{f(t)}{(t-a)^{n+1}}\,dt$

of the coefficients of Laurent series.  Setting to this  $a:=0$,  $f(t):=e^{\frac{z}{2}(t-\frac{1}{t})}$,  $\zeta:=\frac{zt}{2}$  gives

 $c_{n}\;=\;\frac{1}{2\pi i}\oint_{\gamma}\frac{e^{\frac{zt}{2}}e^{-\frac{z}{2t}% }}{t^{n+1}}\,dt\;=\;\frac{1}{2\pi i}\left(\frac{z}{2}\right)^{n}\!\oint_{% \delta}\frac{e^{\zeta}e^{-\frac{z^{2}}{4\zeta}}}{\zeta^{n+1}}\,d\zeta\;=\;\sum% _{m=0}^{\infty}\frac{(-1)^{m}}{m!}\left(\frac{z}{2}\right)^{2m+n}\!\frac{1}{2% \pi i}\oint_{\delta}\zeta^{-m-n-1}e^{\zeta}\,d\zeta.$

The paths $\gamma$ and $\delta$ go once round the origin anticlockwise in the $t$-plane and $\zeta$-plane, respectively.  Since the residue  of $\zeta^{-m-n-1}e^{\zeta}$ in the origin is  $\frac{1}{(m+n)!}=\frac{1}{\Gamma(m+n+1)}$,  the residue theorem  (http://planetmath.org/CauchyResidueTheorem) gives

 $c_{n}\;=\;\sum_{m=0}^{\infty}\frac{(-1)^{m}}{m!\Gamma(m+n+1)}\left(\frac{z}{2}% \right)^{2m+n}\;=\;J_{n}(z).$

This that $F$ has the Laurent expansion (8).

By using the generating function, one can easily derive other formulae, e.g. the of the Bessel functions of integer order:

 $J_{n}(z)\;=\;\frac{1}{\pi}\int_{0}^{\pi}\cos(n\varphi-z\sin{\varphi})\,d\varphi$
 $J_{n}(x\!+\!y)\;=\;\sum_{\nu=-\infty}^{\infty}J_{\nu}(x)J_{n-\nu}(y)$

and the series of cosine and sine:

 $\cos{z}\;=\;J_{0}(z)-2J_{2}(z)+2J_{4}(z)-+\ldots$
 $\sin{z}\;=\;2J_{1}(z)-2J_{3}(z)+2J_{5}(z)-+\ldots$

## References

• 1 N. Piskunov: Diferentsiaal- ja integraalarvutus kõrgematele tehnilistele õppeasutustele.  Kirjastus Valgus, Tallinn (1966).
• 2 K. Kurki-Suonio: Matemaattiset apuneuvot.  Limes r.y., Helsinki (1966).
 Title Bessel’s equation Canonical name BesselsEquation Date of creation 2013-03-22 16:34:57 Last modified on 2013-03-22 16:34:57 Owner pahio (2872) Last modified by pahio (2872) Numerical id 26 Author pahio (2872) Entry type Definition Classification msc 34A05 Classification msc 33C10 Synonym Bessel’s differential equation Synonym Bessel equation Related topic LaplaceEquationInCylindricalCoordinates Related topic CauchyResidueTheorem Related topic PropertiesOfEntireFunctions Related topic FrobeniusMethod Related topic TableOfLaplaceTransforms Related topic BesselFunctionsAndHelicalStructureDiffractionPatterns Defines Bessel’s function Defines Bessel function